1995
DOI: 10.1037/0278-6133.14.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Culturally sanctioned secrets? Latino men's nondisclosure of HIV infection to family, friends, and lovers.

Abstract: Spanish-speaking Latino men (n = 107) were more likely than English-speaking Latinos (n = 85) and Whites (n = 206) to withhold their HIV-positive serostatus and their gay or bisexual orientation from significant others, especially family members. Similar effects were observed when Latinos were divided by birthplace and when analyses controlled for sociodemographic and medical factors. Reasons for revealing or concealing an HIV diagnosis varied across targets. Although both Latinos and Whites were more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(115 citation statements)
references
References 35 publications
12
101
1
1
Order By: Relevance
“…The disclosure of HIV serostatus is frequently associated with emotional and cognitive dilemmas, where LGBT immigrants experience fear and shame and anticipate rejection upon disclosure. Quite often, in fear of shaming and burdening one's family, LGBT immigrants withhold information about their serostatus thus isolating themselves from familial and social supports (Mason et al, 1995). This finding is concerning as social and familial supports were found to have a strong influence on adherence to HIV treatment among HIV positive LGBT immigrants.…”
Section: Living With Hiv/aidsmentioning
confidence: 48%
See 2 more Smart Citations
“…The disclosure of HIV serostatus is frequently associated with emotional and cognitive dilemmas, where LGBT immigrants experience fear and shame and anticipate rejection upon disclosure. Quite often, in fear of shaming and burdening one's family, LGBT immigrants withhold information about their serostatus thus isolating themselves from familial and social supports (Mason et al, 1995). This finding is concerning as social and familial supports were found to have a strong influence on adherence to HIV treatment among HIV positive LGBT immigrants.…”
Section: Living With Hiv/aidsmentioning
confidence: 48%
“…In fact, the majority of immigrant cultures view homosexuality negatively, which decreases the disclosure of information by LGBT immigrants that can be associated with nonheterosexual orientation . For example, research found that LGBT immigrants disclose their HIV-positive serostatus to their friends, family, and sexual partners less often than non-immigrant LGBT people (Mason et al, 1995). Furthermore, negative perceptions of homosexuality in immigrant cultures often prevent LGBT immigrants from sharing their experiences of discrimination and homophobia with friends and family, which is troubling because these types of conversations are often responsible for lower levels of unprotected anal intercourse (Yoshikawa et al, 2004).…”
Section: Sexual Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that HIV disclosure rates in the Midwest are different than that of larger metropolitan cities such as San Francisco, 5,7 Los Angeles, 3,6,8,9 New York, 3 and other larger cities. 10 If it can be accurately assumed that many gay men migrate to larger coastal cities because of issues related to negative family attitudes around their sexual orientation, rates of disclosure to family are like to be lower.…”
Section: Discussionmentioning
confidence: 99%
“…First, most investigations have been crosssectional estimates of percentages of family and friends knowing of the diagnosis at any given point in time. 1,2,6,8,9 Point prevalence studies are important as they provide a quick overview of disclosure patterns at discrete time intervals. Such studies, however, are limited because results would likely vary by how long participants had been diagnosed and in what year the study was conducted.…”
Section: Introductionmentioning
confidence: 99%